Kendali Optimal Penyebaran Penyakit Influenza H1N1 Tiga Strain dengan Vaksinasi dan Pengobatan - Adinda Rizki Kinanti; Nashrul Millah; Irma Fitria (Limits: Journal of Mathematics and Its Applications, 2021)
H1N1 influenza is a respiratory tract infection with common symptoms, namely fever, headache, coughing, and sore throat. H1N1 influenza has several strains known to infect humans, birds, and pigs. Some efforts to overcome the infection of the H1N1 influenza virus are vaccination and treatment. This Research discusses the optimal control in the form of vaccination and treatment applied to the model H1N1 Influenza disease spread. The method used to solve this optimal control problem is the Pontryagin Minimum Principle followed by searching numerical solutions using the Runge-Kutta Forward-Backward Sweep method. Numerical simulations were conducted to compare the spread of H1N1 Influenza before and after optimal control efforts were given. Based on the simulation result, it was shown that giving optimal control in the form of vaccination to susceptible individuals and treatment in individuals infected with three strains could reduce the number of individuals infected with H1N1 Influenza disease .